FRI0467 Development and preliminary validation of the computed tomography sacroiliac structural score (CT-SSS) for assessment of structural lesions in axial spondyloarthritis. (15th June 2017) - Maksymowych, WP; Raynal, M; Loeuille, D; D'Agostino, M-A; Paschke, J; Lambert, RG
Abstract : Background: Computed tomography (CT) is considered the imaging benchmark for the assessment of certain structural lesions in the sacroiliac joints (SIJ) of patients with axial spondyloarthritis (axSpA). Availability of low dose radiation techniques may lead to more widespread use, potentially as a structural endpoint in clinical trials research. Objectives: We aimed to validate a new CT-based scoring method, the CT Sacroiliac Structural Score (CT-SSS), for assessing structural lesions in the SIJ. Methods: CT scans of the SIJ from 44 patients (26 females, mean age 49.4 years, mean symptom duration 9.1 years) were reconstructed in the semicoronal plane parallel to the superior border of the sacrum and scoring of lesions was confined to this plane. Structural lesions were scored in consecutive slices in SIJ quadrants (erosion, sclerosis) or SIJ halves (ankylosis) on a dichotomous basis (present/absent) using the same anatomical principles as developed for the SPARCC MRI SIJ inflammation and structural scores. The most anterior slice is defined as visible joint ≥1cm vertical height and when <3 cm is defined as having only upper iliac and sacral quadrants. A visible joint ≥3cm vertical height is defined as having 4 quadrants. At the posterior aspect of the SIJ, there is a natural separation of iliac and sacral cortical bone by structures in the ligamentary portion. Scoring is terminated when <1cm of iliac and sacral bone is appositional. Two readers independently scored CT scans without a prior calibration exercise and using direct online data entry onto a schematic of the SIJ. Reliability was assessed by kappa statistics, intra-class correlation coefficient (ICC), and Bland-Altman limits of agreement. Results: Scoring was feasible (5–10 minutes per scan) and both ankylosis (ICC=0.95) and erosion (ICC=0.81) were reliably scored (Table). Sclerosis was less reliably scored (ICC=0.39). Presence/absence of ankylosis was reliably detected irrespective of whether this was based on a single slice (κ=0.77) or 3 consecutive slices (κ=0.81). Reliable detection was lower for erosion (κ=0.50 for 1 or 3 slices) and sclerosis (κ=0.44 and 0.48 for 1 and 3 slices, respectively). Bland-Altman graphs illustrate reliability across the range of scores for ankylosis and erosion. Conclusions: The CT-SSS method is feasible and reliable for scoring ankylosis and erosion with minimal calibration. Sclerosis requires further standardization and calibration. Disclosure of Interest: None declared